Matchmoving : the invisible art of camera tracking - Dobbert, Tim (Serious skills., 2013)
Get your foot in the studio door by learning the art of matchmoving Matchmoving is a technique that allows computer graphics to be inserted into live-action footage with correct position, scale, orientation, and motion. Also known as motion tracking, it's what allows movie monsters to run down Main Street and robots to run through crowds--and look real. Now this unique book from a top expert from Industrial Light and Magic teaches you the art of matchmoving. With step-by-step tutorials and pages of examples, this book first explains the basics and then shows you professional.